Innovation capacity, business sophistication and macroeconomic stability: empirical evidence from OECD countries - Kirikkaleli, Dervis; Ozun, Alper (Journal of Business Economics and Management, 2019)
The main aim of this study is to explore the linkages between innovation capacity, business sophistication, and macroeconomic stability within OECD countries. In order to obtain information regarding the relationship between time series variables, the Pedroni cointegration, Kao cointegration, fully modified ordinary least square, dynamic ordinary least square, Granger causality, and Dumitrescu Hurlin causality tests are employed. The empirical results reveal that improvement in business sophistication triggers innovation capacity and support macroeconomic stability. Innovation capacity would also need to be expanded in the long-run, which positively leads to advanced business sophistication that has a cyclical effect. If policymakers intend to accelerate business sophistication, then their attention should be directed towards maximizing the economic indicators in the long-run. To the best of our knowledge, the linkage between innovation capacity, business sophistication and macroeconomic stability in OECD countries has not been comprehensively explored through the use of a single dataset. Thus, the findings of this study could lead to a new debate regarding the concept.